Critical success factors of food and beverages manufacturing small and medium-sized enterprises: a case study approach - Lee, Chun Hui; Yee, Choy Leong (Wuhan University of Technology Press, 2016)
This research aims to explore and understand critical success factors (CSF) of small and medium-sized enterprises (SMEs) in food and beverage (F&B) manufacturing industry. This research focuses on food and beverage industry (F&B) because F&B manufacturing SMEs play a significant role in a country’s economies. However, these SMEs face multiple challenges to gain competitiveness in the marketplace. This research employed multiple case study method and has conducted in-depth interviews with 8 SMEs owners and top management. It has identified 16 CSFs that influence the success of the F&B manufacturing SMEs. Among all, are business strategy, networking, foreign worker management, attractive product packaging, innovation, family capital, business experience, online visibility, access to finance, entrepreneurial orientation, professional management team, effective food safety system, effective quality management system, halal certification, entrepreneurial competencies and supply chain management. The study provides useful guidelines for business owners of SMEs and lays foundation for future research work.